2016
DOI: 10.1007/s12032-016-0784-2
|View full text |Cite
|
Sign up to set email alerts
|

ABO blood groups in relation to breast carcinoma incidence and associated prognostic factors in Moroccan women

Abstract: The association between blood groups ABO and different types of diseases was established in several previous studies. Our aim was to seek the possible association between the ABO blood group and breast cancer-associated prognostic factors. The Chi-squared analytic test was used to compare phenotypic ABO distribution among Moroccan blood donors and 442 cases of women suffering from breast carcinoma with archived files in Maternity Ward of University Hospital C.H.U Ibn Rochd between 2008 and 2011. High incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 51 publications
0
11
0
2
Order By: Relevance
“…Also, a Korean study did not show any difference in the distribution of blood groups of young patients with breast cancer when compared with an age-matched healthy population [ 8 ]. However, a study from Morocco showed that the incidence of breast cancer was increased in patients with blood group type B [ 9 ]. Published data from a meta-analysis showed that Caucasians with blood group type A were at an increased risk of developing breast cancer when compared with non-Caucasians [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, a Korean study did not show any difference in the distribution of blood groups of young patients with breast cancer when compared with an age-matched healthy population [ 8 ]. However, a study from Morocco showed that the incidence of breast cancer was increased in patients with blood group type B [ 9 ]. Published data from a meta-analysis showed that Caucasians with blood group type A were at an increased risk of developing breast cancer when compared with non-Caucasians [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, outros estudos apoiam as associações significativas entre o tipo sanguíneo e o risco de câncer de mama [24][25][26][27] . As razões plausíveis para a disparidade entre os resultados incluem heterogeneidade nas características das populações, tamanhos de estudos limitados e diferenças na distribuição ABO 21 .…”
Section: Resultsunclassified
“…The study by Tryggvadottir et al from Iceland conducted on 184 breast cancers inherited in families and 572 sporadic cases showed the risk of disease to be statistically significant for B blood group carriers 15 . In their study on a population of 442 women in Morocco, Zouine et al report on a high incidence of breast cancers in B blood group women 22 .…”
Section: Discussionmentioning
confidence: 97%